2020
DOI: 10.20944/preprints202003.0242.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Putative Prophylactic Solution for COVID-19: Development of Novel Multiepitope Vaccine Candidate against SARS‐COV‐2 by Comprehensive Immunoinformatic and Molecular Modelling Approach

Abstract: The outbreak of 2019-novel coronavirus (SARS-CoV-2) that causes severe respiratory infection (COVID-19) has spread in China, and the world health organization declared it pandemic. However, no approved drug or vaccines are available, and treatment is mainly supportive and through a few repurposed drugs. In this urgency situation, development of SARS-CoV-2 based vaccines is immediately required. Immunoinformatic and molecular modelling are generally used time-efficient methods to accelerate the discovery and de… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Generally, a protein whose instability index is lesser than 40 are predicted to be stable and values above that predicts the protein as unstable [55]. The stability of the vaccine candidate in this study was found to be better than the recently published multiepitope vaccine candidate against SARS-CoV-2 in which instability index was found higher than the vaccine candidate of this study [56,57]. The theoretical pI of the vaccine was calculated to be 9.96.…”
Section: Immune Simulationmentioning
confidence: 65%
“…Generally, a protein whose instability index is lesser than 40 are predicted to be stable and values above that predicts the protein as unstable [55]. The stability of the vaccine candidate in this study was found to be better than the recently published multiepitope vaccine candidate against SARS-CoV-2 in which instability index was found higher than the vaccine candidate of this study [56,57]. The theoretical pI of the vaccine was calculated to be 9.96.…”
Section: Immune Simulationmentioning
confidence: 65%
“…Though a research group has recently conducted a study like us, it never considered accessory proteins for probable vaccine construction. Rather, the have designed a multi-epitope vaccine from four proteins (Spike, Mpro, RdRp, and Nsp13) of SARS-CoV-2 which showed a lower antigenicity score (0.4259) [ 93 ] when compared to our study.…”
Section: Discussionmentioning
confidence: 94%
“…For instance, spike glycoprotein of SARS-CoV-2 has been evaluated extensively to design different multi-epitope vaccines (Abraham Peele et al., 2020 ; Kar et al., 2020 , Samad et al., 2020 ). Additionally, spike protein has also been used in combination of epitopes from other viral proteins including nucleocapsid and membrane (Kalita et al., 2020 ), protein 8 (Nsp8) and 3 C-like proteinase (Ahmad et al., 2020 ), main protease, Nsp12 (polymerase) and Nsp13 (helicase) (Rehman et al., 2020 ) for construction of peptide-based vaccines. These vaccine candidates were found to be antigenic, non-allergenic and stable in nature, but presence of additional epitopes from other region of S protein or other viral proteins might result into excessive antigenic load along with increased chances of allergenic response.…”
Section: Discussionmentioning
confidence: 99%